Collective Action in Corruption: Analyzing Saiful Ilah's 2020 KPK Operation OTT in Sidoarjo Through a Principal-Agent and Critical Juncture Lens - Nashrulloh, Ahmad (Journal Politique, 2025)
This research aims to describe the corruption mechanism in Sidoarjo that led to Saiful Ilah's 2020 KPK Operation OTT. The authors argue that this case exemplifies how systemic corruption functions as a collective action problem, rooted in principal-agent dynamics, and its persistence reveals insights into the critical juncture following the 2019 KPK Law revision. This study utilizes a descriptive qualitative method, with secondary data sources from judicial records and public reports, and data analysis using established framework of collective action, principal-agent relationships, and critical junctures. The results show that the “fee proyek” system made illegal payments normal and involved many coordinated actors. This shows that corruption continued and adapted even after the legal changes, highlighting how such problems are difficult to stop despite efforts to strengthen anti-corruption measures.